TRUE POLAR WANDER, A SUPERCONTINENTAL LEGACY - Evans D.A. (My University, 1998)
Paleomagnetically determined apparent polar wander (APW) paths should contain components of individual plate motions as well as true polar wander (TPW), the uniform motion of the mantle relative to the spin axis. Quantifying the TPW component for pre-Mesozoic time is hampered by the lack of a representative from the mantle reference frame; nevertheless, TPW can be estimated if all or most of the continents show similar APW paths for a given period of time. Two such estimates have been proposed recently for the early Paleozoic. Plotted relative to Gondwanaland, which may have been drifting over the mantle slowly enough to constitute an approximate mantle reference frame, these TPW swaths are oscillatory and nearly coaxial. A long-lived and stable prolateness of Earth's non-hydrostatic geoid between Cambrian and Devonian time could produce such a pattern of TPW. Similarly oscillatory APW paths exist for the late Neoproterozoic cratons, perhaps indicating TPW about the same long-lived axis during that earlier interval as well. This long-lived prolate axis of Earth' non-hydrostatic figure, representing a stable configuration of mantle mass anomalies, may have been inherited from the vanished Rodinia supercontinent in the same way that the present non-hydrostatic geoid's prolate axis may be a legacy of Mesozoic Pangea and its peripheral subduction zones. These geoidal legacies may endure for several hundred Myr after supercontinental fragmentation, perhaps indicating a characteristic lag time between two distinct geological phenomena: global-scale surface tectonics recorded by the growth and disassembly of supercontinents; and deep mantle convective structure indicated by the long-term record of TPW.
Keywords: GEODYNAMICS; POLAR WANDERING; GONDWANA; PALEOMAGNETISM; GEOID; MANTLE; CONVECTION